Ensuring nutritional security through vegetables - Kalia, Pritam; Gupta, H. S. (Indian Horticulture, 2019)
Introduction: India has made a big leap forward on food front by producing record 257 million tonnes of foodgrains during 2011-12 ensuring adequate availability to its countrymen. On the nutritional security front, however, we have yet to go a long way. On global hunger index (GHI), India stood at 67th rank out of 81 countries assessed during 2011. Over 200 million people in India lack access to adequate food to meet their nutritional requirements and more than 40 per cent of children below the age of 5 year are malnourished. In this scenario, vegetables are attractive alternative crops (including potato, sweet potato, cassava, tapioca, colocasia, yams) capable of providing both food and nutritional security owing to their high yield, energy, nutrient/health-building substances and high potential/ unit land, time and water. In fact, vegetable crops are synonymous to nutritional security. Besides, based on their micronutrient, vitamins, antioxidants and medicinal properties, enhancing their consumption can go a long way in alleviating poverty, dietary deficiency ailments, and hunger. These crops including spices have significant role in export, corporate, contract, organic, cluster and peri-urban farming. Thus, we not only have great potential in improving health of our countrymen, but are also capable of economically empowering them and raising country's GDP, says Dr H.S. Gupta, Director IARI, New Delhi.